2022
DOI: 10.3390/nu14122548
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Eggs in a Plant-Based Diet on Oxidative Stress and Inflammation in Metabolic Syndrome

Abstract: We recently reported that the inclusion of whole eggs in plant-based diets (PBD) increased plasma choline, lutein, and zeaxanthin in individuals with metabolic syndrome (MetS). The objective of the current study was to evaluate whether this dietary pattern would protect against oxidative stress and low-grade inflammation, two common characteristics of MetS. We recruited 24 men and women with MetS, who, after following a PBD for 2 weeks (baseline), were randomly allocated to consume either two whole eggs with 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Two publications reported the results of a crossover RCT where 24 participants with MetS consumed either 2 eggs/day versus yolk-free egg substitute plus 70 g spinach/day for 4 weeks [ 72 , 73 ]. As well as reporting similar metabolic changes to other RCT (higher HDL-c, larger HDL-c particles, higher carotenoids, improved antioxidant status), there was a modest, statistically significant reduction in weight and body mass index.…”
Section: Results: Risk Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Two publications reported the results of a crossover RCT where 24 participants with MetS consumed either 2 eggs/day versus yolk-free egg substitute plus 70 g spinach/day for 4 weeks [ 72 , 73 ]. As well as reporting similar metabolic changes to other RCT (higher HDL-c, larger HDL-c particles, higher carotenoids, improved antioxidant status), there was a modest, statistically significant reduction in weight and body mass index.…”
Section: Results: Risk Assessmentmentioning
confidence: 99%
“…RCT which provided 2–6 eggs daily in healthy [ 75 , 119 , 120 ] and at risk [ 27 ] groups of participants confirmed that eggs do not raise TMAO levels. Similarly, RCT based on daily egg intake found no adverse effects on markers of inflammation or oxidative stress [ 72 , 73 , 120 ]. Indeed, adding whole eggs or egg white to a glucose dietary challenge in prediabetic men attenuated post-prandial oxidative stress [ 121 ].…”
Section: Discussion Of Benefits Vs Risksmentioning
confidence: 99%
“…Our results also exhibited that higher OBS was related to lower MetS severity. The degree of oxidative stress depends on the severity of MetS (51). Previous studies have shown that participants with higher MetS severity scores tended to have less physical activity, a pro-inflammatory dietary pattern, and lower adherence to the Mediterranean diet (52).…”
Section: Discussionmentioning
confidence: 99%
“…Dietary intervention studies in people with MetS indicate the potential therapeutic potential of carotenoids and polyphenols [59][60][61][62][63][64]; however, the results of clinical trials have been inconsistent [65][66][67]. Consuming a balanced and bioactive-rich diet low in carbohydrates and saturated fat is critical to managing metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%